Robotic assisted placement of hepatic artery infusion pump is a safe and feasible approach. Issue 3 (16th August 2016) - Dhir, Mashaal; Zenati, Mazen S.; Padussis, James C.; Jones, Heather L.; Perkins, Samantha; Clifford, Amber K.; Steve, Jennifer; Hogg, Melissa E.; Choudry, Haroon A.; Holtzman, Matthew P.; Zeh, Herbert J.; Pingpank, James F.; et al.
Abstract : Background: Hepatic artery infusion (HAI) chemotherapy can be combined with systemic chemotherapy for the treatment of isolated unresectable colorectal liver metastases (IU‐CRLM) and intrahepatic cholangiocarcinoma (U‐ICC). However, HAI pump placement requires a major laparotomy that may be associated with morbidity. We hypothesized that the computer‐assisted robotic platform would be well suited for this procedure and report the first single institutional case series of robotic assisted HAI pump placement for primary and secondary malignancies of the liver. Methods: A retrospective review of patients who underwent robotic assisted HAI pump placement from January 2008 to January 2016. Peri‐operative outcomes were evaluated. Results: A total of 24 consecutive patients underwent robotic assisted HAI pump placement. Median age was 61 years and 50% were females. Main indications were colorectal cancer = 17 (71%) and intrahepatic cholangiocarcinoma = 4 (17%). The majority (87.5%) of patients had bilobar disease with a median of 6 liver lesions. Concurrent procedures including ablation +/− resection and colectomies were performed in 58% of the patients. Median operative time was 282 min, with median blood loss of 100 ml and length of stay 6 days. Conversion to open was required in one (4%) case. Grade 3 or higher complications were seen in 13% of cases and pump related complications were seen in 21% of patients. All except one HAI pumps could be used for pump chemotherapy. CUSUM analysis of operative time indicated a learning curve of eight cases. Conclusion: Robotic assisted placement of HAI pump placement is safe, feasible, and obviates the need for major laparotomy. J. Surg. Oncol. 2016;114:342–347 . © 2016 Wiley Periodicals, Inc.